2014 IEEE MTT-S International Microwave Symposium (IMS2014) 2014
DOI: 10.1109/mwsym.2014.6848451
|View full text |Cite
|
Sign up to set email alerts
|

Analytical circuit model for stacked slit gratings

Abstract: This work presents a rigorous circuit model to compute the transmission/reflection properties of a finite number of stacked slit gratings printed on dielectric slabs of arbitrary thickness. A key aspect of the present approach is that the circuit model itself leads us to find fully analytical expressions for the finite stacked-grating structure. An analytical model to obtain the Brillouin diagram for the fully periodic structure (infinite number of identical unit cells) is also provided. Index Terms-Bloch wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
(8 reference statements)
1
6
0
Order By: Relevance
“…Two 1D periodic arrays of conducting strips having the same lattice parameter (period p in the figure) are printed at both sides of a dielectric substrate. The case corresponding to h = 0 and w 1 = w 2 has already been considered in [15] and [17]. In contrast to that case, our new problem does not have a vertical symmetry plane, thus precluding the use of the even/odd excitation method employed in the above mentioned references.…”
Section: Derivation Of the Circuit Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Two 1D periodic arrays of conducting strips having the same lattice parameter (period p in the figure) are printed at both sides of a dielectric substrate. The case corresponding to h = 0 and w 1 = w 2 has already been considered in [15] and [17]. In contrast to that case, our new problem does not have a vertical symmetry plane, thus precluding the use of the even/odd excitation method employed in the above mentioned references.…”
Section: Derivation Of the Circuit Modelmentioning
confidence: 99%
“…Since a magnetic wall boundary condition (instead of a grounded metal) at the non-metallized side of the dielectric substrate can be easily incorporated in the model, this method also allows for the analysis of closely spaced identical gratings by means of a superposition of even and odd excitations. Moreover, this strategy makes it possible to solve analytically the problem posed by stacked slit gratings based on identical metallic patterns separated by arbitrary dielectric layers [17]. However, if the slits in both gratings have different width and/or the gratings are shifted with respect to each other (non-aligned gratings), as it is required in some interesting situations [18], the method in [15] cannot be directly applied due to the lack of a symmetry plane.…”
Section: Introductionmentioning
confidence: 99%
“…Although this strategy is useful in many situations, our aim here is to derive the appropriate circuit topology in a rigorous way from first principles and to give the values of the circuit parameters in closed form. This standpoint has been used in the past by some of the authors of the present work to model other periodic structures [35], [49]- [51], and it is now extended to stacked 2D geometries so that the problem under study (multilayer fishnets) can be covered.…”
Section: Circuit Modelingmentioning
confidence: 99%
“…In [51] it was shown that the key aspect that makes it possible to easily obtain an equivalent network for the problem of N stacked metallic slit gratings (1D version of the problem of interest in that paper) comes from the decomposition of the two-coupled metallic screens problem into "internal" and "external" sub-problems as a consequence of the Equivalence Theorem [52]. The extension of this idea to a pair of coupled aperture-type frequency selective surfaces (FSS's) (the most basic form of fishnet structure) is immediate as long as the FSS's are of slot-type nature too (the procedure is not directly applicable to patch-based FSS's).…”
Section: Circuit Modelingmentioning
confidence: 99%
See 1 more Smart Citation